Recommendations for Assessment of Social, Emotional, and Behavioral Health for the National Children's Study - Nowinski, Cindy J.; DeWalt, Darren A.; Carter, Alice S.; Chacko, Anil; Gross, Heather E.; Perrin, Eliana M.; Krug, Chelsea Weaver; Holl, Jane L.; Gershon, Richard C. (Frontiers in Pediatrics, 2021)
The Social Emotional Behavioral (SEB) Team of the National Children’s Study (NCS) was tasked with making recommendations for assessment of important aspects of social-emotional health and function in children. This paper describes the constructs recommended for assessment along with the rationale for their assessment. Measures recommended for use in the NCS were expected to be non-proprietary, brief, psychometrically sound, easy to administer, minimally burdensome to participants, and appropriate for use at planned assessment time points.